Pengujian Konsentrasi Hambat Minimum Ekstrak Daun Mangrove (Avicennia alba Blume) Terhadap Shigella sonnei - Nursyafni; Rahmawati, Ayu; Nurbaiti; Irfan, Nawwar; Nabilla, Alivia (LPPM, Universitas Muhammadiyah Riau, 2024)
Infectious diseases are a public health problem for both developed and developing countries. The cause of an infectious disease such as in Shigella sonnei bacteria which occurs in dysentery is characterized by feces mixed with blood and mucus usually accompanied by fever. One solution to overcome dysentery is by utilizing plants that can be processed into medicine. One of them is mangrove (Avicennia alba Blume) which contains phytochemical compounds as antibacterial activity. This study is an experimental study that aims to determine the minimum inhibitory concentration (MIC) of mangrove leaf ethanol extract (Avicennia alba Blume) against Shigella sonnei bacteria. The minimum inhibitory concentration (MIC) value of the extract was determined using the liquid dilution method and continued with solid dilution, with concentrations of 11%, 12%, 13%, 14%, and 15%. Observations were made to see whether bacterial growth in the media. The test results showed that mangrove leaf ethanol extract (Avicennia alba Blume) had a minimum inhibitory concentration at a concentration of 15% in inhibiting the growth of Shigella sonnei bacteria with clear around the media.